Susceptibility of Pseudomonas aeruginosa Biofilm to Alpha-Helical Peptides: D-enantiomer of LL-37 - Dean, Scott N.; Bishop, Barney M.; Van Hoek, Monique L. (Frontiers in Microbiology, 2011)
Pseudomonas aeruginosa is a highly versatile opportunistic pathogen and its ability to produce biofilms is a direct impediment to the healing of wounds and recovery from infection. Interest in anti-microbial peptides has grown due to their potential therapeutic applications and their possible use against antibiotic resistant bacteria. LL-37 is the only cathelicidin expressed by humans. In this study, we tested LL-37 and the effect of a protease-resistant LL-37 peptide mimetic, the peptide enantiomer D-LL-37, for anti-microbial and anti-biofilm activity against P. aeruginosa. Both forms of the peptide were equally effective as anti-microbial peptides with similar killing kinetics. CD spectra were obtained to demonstrate the chirality of D- and L-LL-37, and the trypsin resistance of D-LL-37 was confirmed. The helical cathelicidin from the cobra Naja atra (NA-CATH), and synthetic peptide variations (ATRA-1, ATRA-2, NA-CATH:ATRA1-ATRA1) were also tested. Although the cobra cathelicidin and related peptides had strong anti-microbial activity, those tested did not inhibit Pseudomonas biofilm formation, neither did control peptides. Both D- and L-LL-37 inhibited the attachment of Pseudomonas to a 96-well plate and decreased the amount of pre-formed (established) biofilm. D-LL-37 is able to promote Pseudomonas motility and decrease biofilm formation by altering the rate of twitching as well as by downregulating the expression of the biofilm-related genes, rhlA and rhlB, similar to L-LL-37. Both L- and D-LL-37 protected Galleria mellonella in vivo against Pseudomonas infection, while NA-CATH:ATRA1-ATRA1 peptide did not. This study demonstrates the ability and equivalence of D-LL-37 compared to L-LL-37 to promote bacterial twitching motility and inhibit biofilm formation, and protect against in vivo infection, and suggests that this peptide could be a critical advancement in the development of new treatments for P. aeruginosa infection.